Research inequities: avoiding the next pandemic - Gomes, Claudia (2020)
COVID-19 has appeared without warning, infecting millions of people worldwide, leading to thousands of deaths and has overcome many countries’ health-care systems.While new future pandemics are predictable, their expansion and impact might be avoided through increasing research to identify and fight infections in low- and middle-income countries, improving countermeasures as a result. While these efforts may not be enough, there is a roadmap to achieve greater understanding of neglected diseases of epidemic or pandemic potential.